2013
DOI: 10.1021/jp411373v
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Molecular Aggregates at a Liquid Interface by Nonlinear Correlation Spectroscopy

Abstract: An analytical model is developed to analyze the fluctuations in the surface second harmonic generation (SHG) intensity from a Langmuir film. From the SHG autocorrelation analysis, also called nonlinear correlation spectroscopy (NLCS), the characteristic times of the phenomena occurring at the interface are determined. This method is then applied to monolayers of the amphiphilic chromophore dye 4-(4dihexadecylaminostyryl)-N-methylpyridinium iodide (DiA) at the air−water interface. This compound is known to spon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 44 publications
(69 reference statements)
0
17
0
Order By: Relevance
“…The result is a sum of A terms only. Gassin et al 37 derived directly the 2D ACF, but, unlike our expression, the proposed equation does not converge to the fluorescence model in the low particle limit.…”
Section: D Diffusionmentioning
confidence: 66%
See 1 more Smart Citation
“…The result is a sum of A terms only. Gassin et al 37 derived directly the 2D ACF, but, unlike our expression, the proposed equation does not converge to the fluorescence model in the low particle limit.…”
Section: D Diffusionmentioning
confidence: 66%
“…caused by the Gouy shift in a focused laser beam 34 . Several papers describe the signal emanating from SHG samples as observed through a multiphoton microscope 24,34-36 , but the interpretation of the autocorrelation function (ACF) of SHG/THG intensity fluctuations has so far been limited to a non-scanning laser beam 19,37 .…”
mentioning
confidence: 99%
“…35 Alternatively, nonlinear correlation spectroscopy (NLCS), specifically second harmonic generation (SHG), was used to track molecular aggregates at a liquid interface. 36-37 Although NLCS is able to detect nanoparticles in a complex biological medium, the methods used to date lack the chemical specificity obtained from measuring the spectrum. SHG is also limited to observing non-centrosymmetric molecules, useful at interfaces, but difficult for bulk measurements.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 More recently, coherent X-ray spectroscopy [13][14][15][16] and nonlinear spectroscopic methods 17,18 have been coupled with correlation analysis. In particular, second harmonic correlation spectroscopy (SHCS) has been used to determine the diffusion coefficient of dye aggregates 17 and long chain para substituted aromatic amphiphiles at a surface. 19 The authors have previously demonstrated the ability of SHCS to determine the binding kinetics of a monovalent interaction between the small molecule (s)-(þ)-1,1'-bi-2-naphthol (SBN) and a 1,2-dioleoyl-sn-glycero-3-phosphocoline (DOPC) lipid bilayer 20 and the more complex interaction between the multivalent proteins cholera toxin b subunit (CTb) and peanut agglutinin (PnA) with monosialotetrahexosylganglioside (GM 1 ) doped DOPC bilayers.…”
Section: Introductionmentioning
confidence: 99%